The effect of mobile money on banking sector stability in Kenya - Samuel Tiriongo; Peter Wamalwa (Kenya Bankers Association (KBA), 2020)
This study examines the effect of mobile money payment service on banking stability in Kenya. Employing data spanning 2007 to 2018, the study builds a model using the generalised method of moment estimation approach of bank stability incorporating its diverse measures - capital adequacy, asset quality, profitability, and liquidity conditions - as a function of the value transacted via mobile money service as well as other market and macroeconomic control variables. Findings show that growth in the value of mobile money transactions has the tendency to reduce capital adequacy and liquidity ratios of banks and increase non-performing loans ratio to total loans, while at the same time support commercial banks' profitability. The divergent implications of the technology-based mobile money innovation on bank stability throws some caution on banks that, before these innovations are adopted, there is need to carefully consider their beneficial effects on profitability against the adverse consequences on capital adequacy, liquidity conditions and quality of assets in the long-run.
Keywords: 330; Elektronisches Geld; Bankenliquidität; Bankrisiko; Kenia